Aktivitas Antioksidan Buah Kopi Hijau Merapi - Isnindar isnindar; Subagus Wahyuono; Sitarina Widyarini; Yuswanto Yuswanto (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Coffee favored because it has flavor, distinctive aroma, and contain bioactive components that can act as an antioxidant. This study aims to determine the antioxidant activity of extracts and fractions of green coffee cherries of Merapi. Green coffee cherries macerated with chloroform further partitioned with 80% methanol solvent. Measurement of antioxidant activity using DPPH spectrophotometric method. The results showed the chloroform extract has antioxidant activity 2.21 mg / mL, the methanol soluble 1.88 mg / mL, the residue was 3.66 mg / mL, and vitamin C 2.38 ug / mL.